We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
167
2
avatar+7 

the negative reciprocal of the sum of all values of x that satisfy the equation x-sqrt(x+1)/x+sqrt(x+1)=11/5

 

Below is my steps but idk if its right

36x2 (x to the power of 2) =162 (16 to the power of 2) (x+1)

and then the 16 to the power of to eventually equals 256x+256

 Jan 1, 2019
 #1
avatar+5795 
+1

\(\text{I assume this is (parens are your friend)}\\ \dfrac{x-\sqrt{x+1}}{x+\sqrt{x+1}}=\dfrac{11}{5}\)

 

\(\text{Let's pull a bit of a trick here}\\ a=\sqrt{x+1}\\ \dfrac{x-a}{x+a}=\dfrac{11}{5}\\ 5x-5a=11x+11a\\ 6x+16a=0\\ 3x=-8a = -8\sqrt{x+1}\\\)

\(9x^2 = 64(x+1)\\ 9x^2 - 64x-64 = 0\\ \text{Using the quadratic formula, (which I leave to you)}\\ x = 8,~-\dfrac{9}{8}\\ \text{Since we squared the equation we must check these roots}\)

 

\(x=8 \Rightarrow a = 3\\ \dfrac{8-3}{8+3} = \dfrac{5}{11} \neq \dfrac{11}{5}\\ \text{8 is a extraneous solution}\\ x=-\dfrac{8}{9}\Rightarrow a = \dfrac{1}{3}\\ \dfrac{-\dfrac{8}{9}-\dfrac 1 3}{-\dfrac{8}{9}+\dfrac 1 3} = \dfrac{11}{5}\\ \text{so }x=-\dfrac{8}{9} \text{ is an actual root, and the only one}\)

 

\(-\dfrac{1}{-\dfrac 8 9} = \dfrac 9 8\)

.
 Jan 1, 2019
 #2
avatar
+1

thank you sooo much

Guest Jan 1, 2019

5 Online Users

avatar
avatar